Nature calls - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Natural resources management in African agriculture: Understanding and improving current practices C B Barrett, F Place & A A Aboud, CABI Publishing, 2002. 368 pp. ISBN 0851995845, GBP 60 Euro 92